Features of educational migration from Kazakhstan to China (Journal of Philosophy, Culture and Political Science, 2026)
The article is devoted to the analysis of educational migration from Kazakhstan to China. According to the authors, educational migration has its pros and cons. This process has several main effects for many countries and for the development of Kazakhstan: political, economic, social and demographic.The purpose of the study is a retrospective analysis of the evolution of educational migration from Kazakhstan to China. To achieve this goal, the historical, socio-economic, cultural, psychological and other prerequisites for the emergence of a student flow in the PRC were studied. The peculiarities of the functioning of the system of international student mobility and the determination of the place of the influx of students from Kazakhstan to China in this system are also revealed; the existing intermediary organizations in Kazakhstan supporting admission to Chinese universities are studied; the role of institutions contributing to the maintenance of student influx and the Republic of Kazakhstan in the host cities of the PRC is shown, the process of adaptation of students to the Chinese environment, the formation of social networks is analyzed. students.Keywords: the international educational migration, the higher education, academic mobility, the Kazakhstan-Chinese relations.